Confirmatory factor analysis of problem-based learning instrument for Office Management and Business Service program - Febrianti, Dika Putri; Hermanto, Febrika Yogie; Nnamdi, Anthony Ogbolu; Rosy, Brillian; Septiana, Nova (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2025)
This study examines the development and validation of a non-test instrument for assessing the Problem-Based Learning (PBL) model in vocational high schools, specifically within the Office Management and Business Services (OMBS) program. The instrument covers seven constructs: problem identification, fact identification, hypothesis formulation, self-directed learning, collaboration and cooperation, solution determination, and evaluation of the problem-solving process. This study uses a quantitative method with a Confirmatory Factor Analysis (CFA) approach to test the validity and reliability of the instrument. Using probability sampling with simple random sampling, 372 respondents (30 teachers and 342 students) from vocational schools in Surabaya participated. Data analysis was conducted using SPSS 16 for reliability testing and LISREL 8.8 for CFA. Results showed high internal consistency (Cronbach's Alpha = 0.949) and satisfactory anti-image coefficients (>0.5), indicating that the data met the requirements for factor analysis. The results of the model fit test also showed that the developed CFA with modification indices model met the criteria for a good fit with a Chi-square value of 170.51 with a degree of freedom (df) of 110, producing a p-value = 0.00019, an RMSEA value of 0.039 <0.08. The validity and reliability of the constructs in each instrument indicator also prove that this model meets a good fit with the resulting value above 0.5. Thus, this non-test instrument is worthy of being used as an assessment standard for evaluating problem-based learning in vocational high schools in the OMBS program to improve the quality of student learning outcomes.